The role of using the balanced scorecard in improving performance in nonprofit organizations:The case study from Egypt - Elgammal, Nihal Ramzy (AUC Knowledge Fountain, 2016)
Any organizations face daily challenges whether they are for-profit or non-profit. They try to achieve their goals by putting a system for monitoring their daily working process with their strategic plan and assessing the outcomes for achieving the organization’s mission. Non-profit organizations differ from profit-driven organizations because they have defined themselves around their mission or services rather than on financial returns. This is why the services provided by such organizations are highly intangible and difficult to measure. The Balanced Scorecard measures the performance of an organization, regardless of its nature, by using four perspectives; tangible asset- Financial and intangible assets; Customer, Internal Process and Learning and Growth in balance to assure that all the work elements are covered. Thus, in light of this concept, the purpose of this study is to explore the relationship between the four perspectives of the Balanced Scorecard and the effective organizational performance and its adaptability to the case study, so that it can adopt the Balanced Scorecard as a strategic management measurement tool for measuring the effectiveness of their performance. The research tested the basic hypothesis which is: There is a significant statistical relationship between improve effective performance of the case study and the use of the Balanced Scorecard perspectives. The results of the statistical analysis of the data showed strongly of the study on that using the Balanced Scorecard can significantly help improve the effective performance of organization